AI VS. REAL TEACHER - Khayrullayeva Makhmuda (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This paper examines the increased application of Artificial Intelligence in the education industry and assesses it on the ability to take the place of conventional teachers. Pros include speed, accuracy, ability to create personalized solutions, but there are no feelings, morality, or cultural aspects in it. The study uses educational psychology and technology integrating the study of education with characteristic features of ethical reasoning. It once again proves that although AI has the capability of lending a helping hand, it cannot replace real teachers entirely. Due to the above-mentioned drawbacks in both fully automated and fully teacher-led approaches towards education, education should go back to a blended model of technology assisted teaching.